2015
DOI: 10.1002/jhm.2406
|View full text |Cite
|
Sign up to set email alerts
|

Is weekend discharge associated with hospital readmission?

Abstract: BACKGROUND: Although recent evidence suggests worse outcomes for patients admitted to the hospital on a weekend, the impact of weekend discharge is less understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
2
9
2
Order By: Relevance
“…In our study there were significantly fewer discharges on the weekend (17.1%) compared to weekdays. This is consistent with the international literature where weekend discharge rates vary between 14.3% and 23.3% . This drop in discharge numbers may be due to reduced hospital staffing levels on the weekend (especially of senior staff) and more restricted access to community services .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study there were significantly fewer discharges on the weekend (17.1%) compared to weekdays. This is consistent with the international literature where weekend discharge rates vary between 14.3% and 23.3% . This drop in discharge numbers may be due to reduced hospital staffing levels on the weekend (especially of senior staff) and more restricted access to community services .…”
Section: Discussionsupporting
confidence: 90%
“…In fact by day 30 there was a significantly lower incidence of adverse outcomes seen in the patients discharged on the weekend. This is consistent with most studies in the literature, which shows non‐inferiority for a weekend discharge and suggests that the enacted policy for discharges from these hospitals on the weekend is too conservative; an important issue to address if we want to improve hospital flow and efficiency.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…2,3 A report from the Bureau of Health Information suggests that in New South Wales, between 14% and 20% of patients discharged with four common clinical conditions (congestive heart failure, pneumonia, acute myocardial infarction and stroke) were readmitted to a different hospital. 4 In fact, non-index hospital readmission rates can exceed 60%; 5 therefore, readmission rates are more meaningful when calculated on unplanned readmissions to all hospitals in a region rather than just the index hospital.…”
Section: Introductionmentioning
confidence: 99%
“… 10 A second study by Cloyd et al reported similar readmission rates among patients with heart failure and pneumonia discharged over the weekend, despite a shorter length of stay (LOS) in hospital and lower availability of outpatient resources. 11 This raises the issue that LOS might be increased by avoiding discharges on the weekend. Previous studies showed that discharging fewer patients over a weekend compared to being discharged on a weekday, resulted in unnecessary increases in the LOS.…”
mentioning
confidence: 99%